Evolution of management models of development as a form of organization of investment and construction activities - Hrabchak, D.; Pelekhatyi, R.; Balaban, O.; Kryvda, K. (Ways to Improve Construction Efficiency, 2024)
The research is devoted to the evolution of management models of development as one of the leading forms of organizing investment and construction activities. The growth of development structures reflects the general transformations in the construction industry, where the interests of investors, clients, contractors, and state institutions intersect. Traditional administrative models, based on centralized planning and hierarchical governance, have lost their relevance under conditions of globalization, digitalization, and intensified competition. Current trends require a transition to integrated management approaches grounded in the principles of project management, strategic partnership, and active use of digital technologies. Of particular importance is the concept of sustainable development, focused on balancing economic efficiency, environmental safety, and social responsibility. The latest practices include the implementation of BIM technologies, digital management platforms, ESG principles, and the development of public-private partnership mechanisms, which together create a foundation for effective interaction among construction process stakeholders. An analysis of modern approaches demonstrates that the competitiveness of development companies directly depends on their ability to adapt to a changing external environment, apply risk management tools, and design long-term development strategies. The proposed structuring of the stages in the evolution of management models highlights the transition from classical administrative systems to innovative digitally oriented ecosystems. Innovative management models not only improve the efficiency of investment and construction activities but also contribute to the harmonious development of the industry, considering economic, social, and environmental dimensions. It should also be emphasized that the transformation of development is closely linked to institutional and regulatory changes, which define the conditions for the implementation of investment projects. The effectiveness of management depends not only on internal organizational decisions but also on the ability of companies to integrate into a broader socio-economic space that encompasses market, legal, and innovative factors.